2018
DOI: 10.21776/ub.mps.2018.004.02.4
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy dan Optimisme sebagai Prediktor Subjective Well-Being pada Mahasiswa Tahun Pertama

Abstract: This study examined self-efficacy and optimism in predicting subjective well being of firstyear undergraduate students. Participants were first-year undergraduate students of UIN Sultan Syarif Kasim Riau (N=372; 121 males, 251 females). Participants completed the Positive and Negative Affect Schedule (PANAS), Satisfaction With Life Scale, General Self-Efficacy Scale and Life Orientation Test-Revised (LOT-R). Multiple regression analysis was conducted to examine how the predictors contribute to subjective well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Total scores of GSES ranged from 10 to 40. Our prior investigation found that the Indonesian version of GSES has a good validity and reliability (see Novrianto & Marettih, 2018;Novrianto et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Total scores of GSES ranged from 10 to 40. Our prior investigation found that the Indonesian version of GSES has a good validity and reliability (see Novrianto & Marettih, 2018;Novrianto et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The higher the total score for the item set, the higher the level of positive or negative affect during the time period. In this study, the researcher used the Indonesian version of PANAS that was adapted by Novrianto and Marettih (2018). The adaptation process follows the guideline developed by Beaton et al (2000).…”
Section: Methodsmentioning
confidence: 99%
“…Self Efficacy didefenisikan sebagai keyakinan diri seseorang terhadap kemampuannya dalam mengambil Langkah yang tepat untuk meraih apa yang di cita-citakan (Bandura, 1997). Self Efficacy dan optimisme memiliki peran penting dalam memprediksi Subjektive Wellbeing pada mahasiswa (Novrianto & Marettih, 2018). Terdapat hubungan positif antara Self Efficacy dan Subyektive Wellbeing pada mahasiswa (Ardipal, Ayu Niza Machfauzia, 2020).…”
Section: A Pendahuluanunclassified